تحجير المباح في شروط عقد الزواج: دراسة مقارنة - سليمان، نشوان محمد; الطائى، فادية عدنان حسن (جامعة كركوك - كلية القانون والعلوم السياسية, 2017)
Islamic Sharia (body of Islamic laws) has established the interests of people in living and the hereafter, thus it combined the interest of the life and the afterlife. Since the texts of the Islamic sharia are infinite, the events are infinite. Therefore, the wisdom of Allah stipulated to endow the Sharia with certain characteristics that render then suitable for every time and every place. The most important of these characteristics that is most flexible through which Sharia could comprehend all the newly occurring things is the necessity of jurisprudence in accordance with sharia policy rules in every issue of relevance to the lives of people. The jurisprudents have based these issues on sharia principles and rules that are deemed as the base of the hardening of the allowed which are going to discuss. According to the principle of deed consequences, the sent interest, and other principles. Undoubtedly, that period has occurred many social phenomena that relate the life of family and then society as whole. Therefore, dealing with these new things is the essence of maintaining the necessities which is through the intervention in these unprohibited things by obliging people to find solution to the new issues that were not stipulated about by the Legislator, like prohibiting the marriage between relatives because of genetic diseases in the family that effect negatively the new generation provided it is proven in medical examination. Therefore, the theme of this study is based on maintaining the general interests which is the basis that should be used in the policy of hardening the allowed. The conclusion comes up with the most important findings of the study and recommendations.
أقامت الشريعة الإسلامية على مصالح العباد في المعاش والمعاد، وهي بذلك جمعت بين مصالح الدنيا والأخرة، وبما أن نصوص الشريعة الإسلامية متناهية فإن الحوادث غير متناهية لهذه اقتضت حكمة الله سبحانه وتعالي أن تختص هذه الشريعة بمزايا تجعلها صالحة لكل زمان ومكان. وأهم هذه المزايا هي المرونة التي بفضلها يمكن للشريعة الإسلامية استيعاب جميع المستجدات من الأمور، مما يرشد الفقهاء المعاصرين إلى ضرورة الاجتهاد على وفق أحكام السياسة الشرعية في كل مسألة من المسائل التي تمس حياة الناس، وقد استند الفقهاء في هذه المسألة إلى مبادئ وقواعد شرعية تعتبر من المستندات الهامة لسياسة تحجير المباح التي سوف نخص به موضوع البحث، بالاعتماد على مبدأ مآلات الأفعال، والمصالح المرسلة، وغير ذلك من المبادئ العامة ومقاصد الشريعة، ولاريب إن هذا العصر حصلت فيه متغيرات كبيرة غيرت أنظمة الحياة وأوضاع الناس وتولد عنها ظواهر اجتماعية عديدة تمس حياة الأسرة ومن ثم المجتمع ككل، لذلك فإن التعامل مع هذه المستجدات يكون محوره الحفاظ على الضروريات الذي يكون عن طريق التدخل بهذه المباحات من خلال إلزام الناس بتطبيق أو منع أو وجوب ما يصدر من تشريعات يكون لها الأثر في إيجاد الحلول لكل مسألة جديدة لم يرد بشأنها نص خاص من الشارع، أو التي لم يسبق أن بحثها الفقهاء القدامى مثل مدى إيجاب الكفاءة في أمور لم يكن متعارف عليها في زمن سابق لبساطة الحياة آنذاك، أو منع أو تقيد الزواج من الأقارب إذا ثبت بالفحص الطبي وجود أمراض وراثية في العائلة تؤثر سلباً على الجيل الجديد ومن ثم على المجتمع ككل لذلك فإن موضوع البحث يبني على الحفاظ على المصالح العامة التي تكون من الأساسيات التي يجب الاعتماد عليها في عمل سياسة تحجير المباح عليماً بأننا سنبين في كل فقرة من هذه الفقرات الموقف الفقهي والقانوني، وفي ختام هذا البحث توصلنا إلى عدد من النتائج والتوصيات راجين من ذلك التوفيق من الله تعالي.
Keywords: القوانين والتشريعات -- الفقة الاسلامى -- عقود الزواج